Laser cooling and electronic structure studies of CaK and its ions CaK± - Amal Moussa; Nayla El-Kork; Mahmoud Korek (New Journal of Physics, 2021)
Aiming at a laser cooling investigation, we have used ab initio complete active space self consistent field (CASSCF)/(MRCI +Q) calculations to study the electronic structure of the diatomic molecule CaK and its molecular ions CaK ^+ and CaK ^− . The potential energy curves and the static dipole moment curves have been investigated for the considered molecules along with the spectroscopic constants T _e , ω _e , B _e , and R _e , in addition to the values of dipole moment μ _e and dissociation energy D _e . Overall, 19 and 14 electronic states have been studied respectively for CaK, CaK ^+ , from which 12 for CaK and six for CaK ^+ have been investigated here for the first time. Our obtained results agree well with data related to states that have been previously examined. Nineteen electronic states have been explored for CaK ^− , which up to our knowledge have not been previously calculated. The transition dipole moments have been calculated for the lowest Σ ^+ –Σ ^+ and Σ ^+ –Π transitions along with the Franck–Condon factor, Einstein coefficient, the spontaneous radiative lifetime, and the emission oscillator strength corresponding to the investigated transitions. A ro-vibrational analysis has been done via the canonical function approach, where the vibrational parameters E _v , B _v , D _v, and the turning points R _min and R _max have been determined. These calculations showed that the molecule CaK is a suitable candidate for Doppler laser cooling, and we propose a laser cooling scheme to this end. The Doppler limit temperature T _D and recoil temperature T _r have values as low as T _D = 51 μ K and T _r = 156 nK. The results should provide a useful reference for experimental spectroscopic and ultra-cold molecular physics studies.